Understanding the interaction between bonding strength and strain distribution of plywood. (April 2020) - Li, Wanzhao; Zhang, Zheng; Zhou, Guoqiang; Leng, Weiqi; Mei, Changtong
Abstract: Plywood is an important engineered wood product manufactured by orthotropically bonding veneers together. Bonding strength plays a crucial role in the performance of plywood. However the interaction between bonding strength and strain distribution has not been fully understood yet. Therefore, in this study, relationships between bonding strength and shear strain distribution in six types of plywood were illustrated using digital image correlation (DIC) approach as performing the lap-shear tests. Both urea formaldehyde (UF) and phenol formaldehyde (PF) resin were used as the bonding adhesive. Fluorescence microscopy was adopted to visualize the resin distribution within the micro-structure of the specimens. Results showed that the failure load (FL) of plywood positively and negatively correlated to the quantity of UF and PF resin, respectively. Increased quantity of UF resin facilitated to form a consecutive bond line, while large quantity of PF resin made the specimens brittle. Large ratio between load and strain, and homogenous strain distribution contribute to the high FL. Strain starts in regions adjacent to the notches and transfers to the remaining areas in the region of interest (ROI) by smoothly crossing the bond line. The properties of wood veneers play an important role in the bonding strength as strain is more likely to be started from the veneers. Findings of this study can contribute to the improvement of design strategies aiming the enhancement of the mechanical properties of plywood with small amount of resin.